Modélisation par éléments finis du comportement mécanique de structures textiles : de la fibre au tissu - Durville, Damien (European Journal of Computational Mechanics, 2002)
In this paper, an approach of the modelling of contact-friction interactions between beams in large transformations is proposed in order to model the behavioru of textile structures by taking into account the contacts which occur at a mesoscopic scale between the elementary fibres or wires. This approach is based in particular on the determination of a geometrical support for the domain of interaction and an independant discretization of this one. The generated contact elements are integrated naturally into a finite element formulation. Numerical examples which highlight complex non-linear phenomena in wires and samples of woven fabrics are given to show the relevance of the method.